Fruit crops of india - R.G Maiti; R.G Maiti (Ludhiana Kalyani, 2004)
The book contains plenty of material which will be useful for the studets of agricultural universities and research institutes, as wel as extention workers,who are working in the field of fruiy culture
Tropical fruits sub-tropical fruits temperate fruits
Keywords: Tropical fruits, sub-tropical fruits, temperate fruits